Joining of sintered NdFeB permanent magnet to steel using novel Zn-Sn-Bi-Nd alloy: Microstructure and soldering mechanism. (July 2021) - Luo, Cui; Qiu, Xiaoming; Su, Jinlong; Xu, Yuxin; Zhao, Xiaohui; Xing, Fei
Highlights: A novel Zn-Sn-Bi-Nd alloy was successfully developed for soldering steel to sintered NdFeB permanent magnet. As Prolonging holding time or increasing soldering temperature, the shear strength increased first and then decreased. The maximum shear strength reached 110.7 MPa at 430 °C for 30 s. Abstract: The steel and sintered NdFeB permanent magnet were successfully connected by a novel Zn-Sn-Bi-Nd alloy. The effects of the soldering temperature (410–450 ° C) and holding time (20−40 s) on the microstructure and mechanical properties of soldered joints were investigated. The results showed that element Zn diffused to the surface of sintered NdFeB permanent magnet, with the formation of ξ -FeZn13 /NdFe5.5 Zn(B) interfacial layer. Meanwhile, the multilayered Γ-Fe3 Zn10 /δ-FeZn10 / ξ -FeZn13 phases were observed at the steel side. As prolonging holding time or increasing soldering temperature, the reaction layer grew thicker. The shear strength increased first and then decreased. Therefore, the maximum shear strength (110.7 MPa) was obtained at 430°C for 30 s. Proper reaction layer thickness is beneficial to the improvement of shear strength.